Circular Economy in ASEAN: Another Rough Road Ahead - Mulyaman, Darynaufal; Alfachridzi, Emir (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 1 (2024): JURNAL DIKSHI, 2024)
Circular economy (CE) has become a priority agenda for ASEAN in recent years. In October 2021, ASEAN officially launched the Framework for Circular Economy to encourage the transition towards a more sustainable economic model in the region. However, the implementation of CE in ASEAN still faces several challenges. Firstly, there are differences in economic development levels and technical capabilities between member countries in implementing CE standards and policies. Developed countries tend to be more aggressive in setting resource efficiency targets, while developing countries require a more gradual transition. Secondly, the harmonization of CE standards is often hampered by conflicts of interest among policymakers due to political and economic pressures. Thirdly, market demand for eco-friendly products remains low in ASEAN. Fourthly, circular economic practices remain fragmented across industrial sectors and value chains. This paper aims to analyze these challenges through a qualitative descriptive approach, referring to current literature and statistical data. The analysis focuses on aspects of CE standards harmonization in the context of varying ASEAN economic development levels and global political economic dynamics. This study is expected to provide policy recommendations to overcome the challenges of implementing CE effectively and equitably in ASEAN.